FAILURE ANALYSIS IN HYDRODYNAMIC IMPACT NUMERICAL SIMULATION - Hakim, Raihan
Indonesia is making the N219 amphibious aircraft with a twin-float configuration capable of landing on land and water. This aircraft is made to reach remote islands that do not have aircraft landing facilities. An important structure in the manufacture of this aircraft is the floating structure, where this part must be able to withstand a large enough hydrodynamic impact load when landing on water. To get a strong float structure, a numerical analysis can be done to investigate the floating structure that is prone to failure. In this study, numerical simulation modeling of hydrodynamic impact based on an experiment was carried out to obtain the same failure results as the experiment. If this numerical simulation modeling succeeds in producing results that are in accordance with the experiment, this modeling method can be used for numerical analysis modeling of float structures in the future. The experiment was carried out by dropping a thin aluminum plate and its supports into the water, failing in the middle of the plate. To model this experiment, the software used is ABAQUS/CAE and the Coupled Eulerian-Lagrangian method is used. To model the failure, the ductile damage property will be defined. From the comparison of the results, the results of the numerical simulation can replicate the failure form and the maximum acceleration value obtained by the experiment. Thus, the modeling method in this study can be used to analyze failures in float structures.